THE ROLE OF MEDIATION OF KNOWLEDGE SHARING IN LEARNING ORGANIZATION AND EMPLOYEE PERFORMANCE - Conchita V. Latupapua; Harvey Hiariey; Pieter Novry Ruddy Rehatta; Adelvia Pentury (Jurnal Ekonomi, 2023)
In the current era, hospitals take an important role in overcoming various health problems, especially their function as public servants. The development of organizations today is faced with various very rapid advances, therefore hospital employees are required to carry out efforts to store and disseminate knowledge well. The purpose of this study is to test and analyze the role of Knowledge Sharing as a mediator of Learning Organization on Employee Performance. With a total population of 197 and sampling techniques using simple random sampling techniques by calculating slovin totaling 66 employees of RSUD in Ambon City. The analytical test tool used is Smart PLS 3.0 with SEM (Structural Equation Modeling) analysis method. The results of this study show that learning organization has an effect and is significant on Knowledge sharing but not significant on employee performance. Partially, knowledge sharing also affects employee performance.